Identification of a reverse crossover point during moderate-intensity exercise (>6 h; 69% VO2max) in a world-class triathlete - A secondary analysis - Noakes, T.; Buga, A.; Volek, J.; Prins, P. (Frontiers in Nutrition, 2025)
The crossover point (COP) refers to the increase in CHO oxidation with increasing exercise intensity (1) which posits that, at any exercise intensity above 85%, zero energy can come from fat oxidation. This is the basis for the belief that CHO is the obligatory fuel for high intensity exercise (2) and that muscle glycogen depletion in the active muscles is the favored explanation for the fatigue that develops during prolonged exercise (3-5).